HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN PERAWAT DALAM MENJALANKAN EARLY WARNING SCORE DI RUMAH SAKIT BIMC KUTA - I Gusti Bagus Artha Pradnyana; I Made Dwie Pradnya Susila; Nina Rismawati Hakim (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Early Warning Score (EWS) is an early warning system starting from early detection, making decisions before the patient experiences an emergency condition. The parameters in the EWS method are level of consciousness, respiration or exhalation, oxygen saturation, supplemental oxygen, temperature, pulse rate, and systolic blood pressure. The purpose of this study was to determine the correlation between knowledge level and nurse compliance of nurses in carrying out early warning score at BIMC Hospital Kuta. The EWS assessment is supported by nurses’ education level and work experience. This study used a cross-sectional approach correlation design with a total sampling technique of 58 nurses. In this study, it was found that the good knowledge level of nurses at BIMC Hospital Kuta was 86.2%, while the compliance level of nurses in carrying out the early warning score was found that the nurses obeyed in carrying out an early warning score of 86.2%. Data processing used the chi square statistical test. The results of the statistical test p value 0.000, which showed that there was a significant correlation between knowledge level and nurse compliance in carrying out the early warning score and r value = -0.619.